Repeat Flow Diversion for Cerebral Aneurysms Failing Prior Flow Diversion: Safety and Feasibility From Multicenter Experience. Issue 4 (12th October 2021) - Salem, Mohamed M.; Sweid, Ahmad; Kuhn, Anna L.; Dmytriw, Adam A.; Gomez-Paz, Santiago; Maragkos, Georgios A.; Waqas, Muhammad; Parra-Farinas, Carmen; Salehani, Arsalaan; Adeeb, Nimer; Brouwer, Patrick; Pickett, Gwynedd; et al.
Abstract : Background: Aneurysmal persistence after flow diversion (FD) occurs in 5% to 25% of aneurysms, which may necessitate retreatment. There are limited data on safety/efficacy of repeat FD—a frequently utilized strategy in such cases. Methods: A series of consecutive patients undergoing FD retreatment from 15 centers were reviewed (2011–2019), with inclusion criteria of repeat FD for the same aneurysm at least 6 months after initial treatment, with minimum of 6 months post-retreatment imaging. The primary outcome was aneurysmal occlusion, and secondary outcome was safety. A multivariable logistic regression model was constructed to identify predictors of incomplete occlusion (90%–99% and <90% occlusion) versus complete occlusion (100%) after retreatment. Results: Ninety-five patients (median age, 57 years; 81% women) harboring 95 aneurysms underwent 198 treatment procedures. Majority of aneurysms were unruptured (87.4%), saccular (74.7%), and located in the internal carotid artery (79%; median size, 9 mm). Median elapsed time between the first and second treatment was 12.2 months. Last available follow-up was at median 12.8 months after retreatment, and median 30.6 months after the initial treatment, showing complete occlusion in 46.2% and near-complete occlusion (90%–99%) in 20.4% of aneurysms. There was no difference in ischemic complications following initial treatment and retreatment (4.2% versus 4.2%; P >0.99). On multivariable regression, fusiform morphology had higher nonocclusion odds after retreatment (odds ratio [OR], 7.2 [95% CI, 1.97–20.8]). Family history of aneurysms was associated with lower odds of nonocclusion (OR, 0.18 [95% CI, 0.04–0.78]). Likewise, positive smoking history was associated with lower odds of nonocclusion (OR, 0.29 [95% CI, 0.1–0.86]). History of hypertension trended toward incomplete occlusion (OR, 3.10 [95% CI, 0.98–6.3]), similar to incorporated branch into aneurysms (OR, 2.78 [95% CI, 0.98–6.8]). Conclusions: Repeat FD for persistent aneurysms carries a reasonable success/safety profile. Satisfactory occlusion (100% and 90%–99% occlusion) was encountered in two-thirds of patients, with similar complications between the initial and subsequent retreatments. Fusiform morphology was the strongest predictor of retreatment failure.